Contribution from different domains for creativity management in the context of innovation - Wielewicki, Patrícia; Roda, Rui Ferreira (Revista de Negócios, 2018)
Creativity is an ever-increasing theme of interest in the context of management due to its importance for the innovation process. Current literature suggests that the interaction between the concepts of innovation and creativity is not clear. Both phenomena are cognitive and nebulous concepts and therefore are difficult to access by traditional research approaches. Considering creativity management in the scope of innovation processes faced by organizations, this study aims at contributing for the clarifying the relation between creativity and innovation by analyzing it under the point of view of the three domains: design, haute cuisine and art. That research strategy is based on the need for a systemic view of creativity, standing out the growing interest in the field of creativity for the study of processes in different domains. The study articulates two investigation methods structured in two parts: (i) literature review and (ii) systematic literature review. Both methods are bound to the construction of aÂ theoretical framework which points outÂ contributesÂ of the studied domainsÂ for the optimization of creative processes in the organizational context. The study suggests the existence of three integrated models of creativity management in the context of innovation, each one referring to a given domain analyzed. The framework presented is featured as a contribute for enterprises in the search for new creativity management models for innovation, as well as a starting point for the conception of a more robust theoretical body for the study of different creative processes in different domains in the context of innovation.